The dependence of the internal electrical resistance of the cable rubber rope on the presence of a cable rupture - Іван Бельмас; Олена Білоус; Ганна Танцура; Ангеліна Швачка (Mechanics and Advanced Technologies)
Problems. The introduction of steel reinforced concrete coatings of structures, in our opinion, is preceded by the development of methods for monitoring the state of cable-stayed ropes - creating safe conditions for long-term operation of structures.